Managerial Alignment versus Entrenchment Effects on Firm Performance in Australia - Singhchawla, Wanachan; Evans, Robert; Evans, John; Rajabhat, S. (Taiwan Institute of Business Administration, 2011)
This study investigates whether managerial share ownership serve to enjhance or detract from firm performance in listed companies in Australia. The results support both the 'convergence of interest' and 'entrenchment' hypotheses and therefore, the existence of a non-linear relationship between firm performance and managerial ownership. A cubic relationship is found to exist for Australian data, namely convergence to entrenchment to convergence, with maximum and minimum points occurring at approximately 12% and 58% of executive directors' shareholdings, respectively.